1984
DOI: 10.1007/bf00656836
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of cold work on the oxidation behavior of some austenitic stainless steels: High temperature oxidation

Abstract: AISI 304, 314, 321, and Incoloy 800H have been subjected to several pretreatments: polishing, milling, grinding, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…This is consistent with cold-work-induced formation of a a 0 -martensite and its higher associated defect density that extended into the adjacent oxide, creating easy diffusion paths. Although the initial oxidation rate of coldworked 304 stainless steel is higher, faster diffusion would ultimately result in a higher-density, more protective Crrich oxide than in non-cold-worked alloys, hence slowing the oxidation rate [22,25]. It should be noted that no a 0 -martensite was observed during this study.…”
Section: Influence Of Cold Work On Surface Oxidationmentioning
confidence: 79%
See 1 more Smart Citation
“…This is consistent with cold-work-induced formation of a a 0 -martensite and its higher associated defect density that extended into the adjacent oxide, creating easy diffusion paths. Although the initial oxidation rate of coldworked 304 stainless steel is higher, faster diffusion would ultimately result in a higher-density, more protective Crrich oxide than in non-cold-worked alloys, hence slowing the oxidation rate [22,25]. It should be noted that no a 0 -martensite was observed during this study.…”
Section: Influence Of Cold Work On Surface Oxidationmentioning
confidence: 79%
“…Cold work, in particular, was found to be beneficial in the long term, increasing oxidation resistance in 304 stainless steels [26]. Langevoort's work showed a small influence of cold work on the oxidation behaviour of 304 stainless steel under atmospheric and ultrahigh-vacuum conditions [25][26][27]. He found that cold work did not alter the oxidation mechanisms or the oxide compositions but only affected the diffusion rates through the oxide as well as through the metal, changing the oxidation rates.…”
Section: Influence Of Cold Work On Surface Oxidationmentioning
confidence: 96%
“…This particular behavior was attributed to the presence of surface imperfections massively introduced by mechanical working that served as nucleation sites for initial oxide formation, leading to a fine scale microstructure, a rapid diffusion of Cr ions across the scale layer along grain boundaries, and therefore a larger k p . Although limited research has been reported for Cr 2 O 3 growth under different surface conditions, Kuiry [11] and Longevoort [12] have shown that the oxidation rate of austenitic stainless steels was initially faster and started earlier when cold mechanical work was previously applied on the sample. Taking these observations into account, it is reasonable to argue that the high level of surface deformation introduced by hot rolling led to a large density of oxide nucleation sites and a fine oxide grain structure, ultimately increasing the value of the parabolic rate constant of Cr 2 O 3 growth during the initial stages of selective oxidation.…”
Section: Effect Of Surface Statementioning
confidence: 98%
“…Several researchers [11,12,14] have shown that the application of cold mechanical working has led to a net protective effect on the austenitic stainless steel, establishing more rapidly protective oxidation conditions. It can be suggested that the increase in the factor k p /D associated to hot rolling was much higher than that under cold working conditions as a consequence of the high sensitivity of k p to the presence of surface imperfections.…”
Section: Effect Of Surface Statementioning
confidence: 99%
“…Due to cold work a phase transformation occurs in which some martensite formation takes place in the austenitic grains. The grain boundaries between the austenite and martensite grains show a very high diffusivity for Cr and Fe [21], explaining the increase of the oxidation resistance of AISI 304 as a result of cold work [1, 2,22].…”
Section: Influence Of Cold Workmentioning
confidence: 99%